Greenwashing or Greenhushing?: A Quasi-Experiment to Correlate Green Behaviour and Tourist’s Level of Trust Toward Communication Strategies in Volunteer Tourism’s Website - Anggita Swestiana; Hendrie Adji Kusworo; Chafid Fandeli (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2022)
Volunteer Tourism (VT) is introduced as a form of tourism that gives benefits for both tourists and locals. Even though it has a sustainable goal, VT undergoes the greenwashing’s claim because of its marketing strategies. Moreover, the long-term effect of this phenomenon causes distrust among tourists and postpones the development of sustainable tourism products. This research offers greenhushing as an alternative strategy for under-developed VT’s operator which cannot implement a vocal green strategy. In this research, greenwashing and greenhushing strategies are tested and correlated with the tourist’s green behaviour using a quasi-experimental design. The participants of this research are the international students of Universitas Gadjah Mada, Yogyakarta. The results of this research are there are differences between the greenwashing and greenhushing strategies in gaining trust among tourists. Furthermore, the greenhushing is more trustworthy than the greenwashing.